Carboxylated nanodiamonds can be used as negative reference in in vitro nanogenotoxicity studies. Issue 8 (6th February 2017) - Moche, H.; Paget, V.; Chevalier, D.; Lorge, E.; Claude, N.; Girard, H. A.; Arnault, J. C.; Chevillard, S.; Nesslany, F.
Abstract: Nanodiamonds (NDs) are promising nanomaterials for biomedical applications. However, a few studies highlighted an in vitro genotoxic activity for detonation NDs, which was not evidenced in one of our previous work quantifying γ‐H2Ax after 20 and 100 nm high‐pressure high‐temperature ND exposures of several cell lines. To confirm these results, in the present work, we investigated the genotoxicity of the same 20 and 100 nm NDs and added intermediate‐sized NDs of 50 nm. Conventional in vitro genotoxicity tests were used, i.e., the in vitro micronucleus and comet assays that are recommended by the French National Agency for Medicines and Health Products Safety for the toxicological evaluation of nanomedicines. In vitro micronucleus and in vitro comet assays (standard and hOGG1‐modified) were therefore performed in two human cell lines, the bronchial epithelial 16HBE14o– cells and the colon carcinoma T84 cells. Our results did not show any genotoxic activity, whatever the test, the cell line or the size of carboxylated NDs. Even though these in vitro results should be confirmed in vivo, they reinforce the potential interest of carboxylated NDs for biomedical applications or even as a negative reference nanoparticle in nanotoxicology. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : In the present work, we investigated the genotoxicity of 20, 50 and 100 nm high‐pressure high‐temperature nanodiamonds. We performed in vitro micronucleus assays and in vitro comet assays (standard and hOGG1‐modified) in two human cell lines, the bronchial epithelial 16HBE14o– cells and the colon carcinoma T84 cells. Our results did not show any genotoxic activity, whatever the test, the cell line or the size of nanodiamonds.